Corporate law and economic analysis / edited by Lucian Arye Bebchuk. - Bebchuk, Lucian A. (Cambridge University Press, 1990)
This collection uses economic analysis to study some of the most pressing issues in corporate law. The last decade has brought certain corporate transactions and arrangements to the forefront of public attention and public debate. At the same time, a new mode of corporate law analysis has been developed - one that uses the tools of economics to identify the consequences and desirable features of corporate law rules. By bringing together work at the frontier of this method of analysis, the volume provides a good picture of the power, current state, and future direction of the economic analysis of corporate law. Written by some of the most prominent contributors to the field, many of the chapters focus directly on the corporate control transactions that have recently attracted the most interest and controversy - corporate takeovers, buy-outs, recapitalizations, and reorganizations.